Aspek-Aspek Kritis Dunia "Kaum Ketiga" - Koeswinarno, Koeswinarno (Musawa Jurnal Studi Gender dan Islam, 2003)
Nowadays in some advanced countries homosexuality is being given increasing social acknowledgement compared to previous times. Here in Indonesia there are a small number of homosexuals who have started to open up socially. This article analyses the tendencies of "other homosexuals" - that is, transvestites and transsexuals, and tries to understand their world from the inside. Up to now the majority of society still tends to negatively stereotype them, making their life marginalized, even though socially they are far more open compared to homosexuals. For this reason we need to face the issue of transvestites with a perspective of wisdom.